2016
DOI: 10.4239/wjd.v7.i19.523
|View full text |Cite
|
Sign up to set email alerts
|

Implanting 1.1B4 human β-cell pseudoislets improves glycaemic control in diabetic severe combined immune deficient mice

Abstract: AIMTo investigate the potential of implanting pseudoislets formed from human insulin-releasing β-cell lines as an alternative to islet transplantation.METHODSIn this study, the anti-diabetic potential of novel human insulin releasing 1.1B4 β-cells was evaluated by implanting the cells, either as free cell suspensions, or as three-dimensional pseudoislets, into the subscapular region of severe combined immune deficient mice rendered diabetic by single high-dose administration of streptozotocin. Metabolic parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Importantly, pseudoislet cellular configuration may provide an especially good alternative for isolated islets. The remarkable augmentation in insulin secretion compared with correspondent monolayers in response to secretagogues following homotypic PIs formation was observed with MIN6 [ 12 , 14 , 15 , 44 , 45 ], 1.1B4 [ 21 ], or EndoC-βH1 [ 46 , 47 ] cell lines. The enhanced cell-cell contact within PIs was connected with increased calcium signaling, increased E-cadherin levels, and connexin 36 regulating cellular communication and islet architecture [ 12 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, pseudoislet cellular configuration may provide an especially good alternative for isolated islets. The remarkable augmentation in insulin secretion compared with correspondent monolayers in response to secretagogues following homotypic PIs formation was observed with MIN6 [ 12 , 14 , 15 , 44 , 45 ], 1.1B4 [ 21 ], or EndoC-βH1 [ 46 , 47 ] cell lines. The enhanced cell-cell contact within PIs was connected with increased calcium signaling, increased E-cadherin levels, and connexin 36 regulating cellular communication and islet architecture [ 12 , 45 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only example of GPCRs studied so far in pseudoislet models is the glucagon-like peptide-1 receptor (GLP1R). Green et al showed that the GLP1R gene was significantly upregulated in pseudoislets formed by human 1.1B4 β cells compared to monolayers [ 21 ]. Similarly, higher levels of GLP1R accompanied with better responsiveness to exendin-4 were demonstrated in PIs formed by co-culture of the human EndoC-βH1 β-cell line and murine MS1 endothelial cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous aggregation and hanging-drop methods have been the standard for generating pseudoislets for over a decade [22, 24, 25, 2830], and more complex strategies (generally employing gravity-mediated settling) have recently been reported. Where efficiency has been reported, it has generally been low due to high cell loss during the process, which would nullify any potential benefit brought about by reaggregation [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In this study we were able to rapidly, efficiently and reproducibly generate size-controlled CFA-PI from donated human islet material from 21 different donors, obtained from three different distribution programmes across North America. Spontaneous aggregation and hanging-drop methods have been the standard for generating pseudoislets for over a decade [ 22 , 24 , 25 , 28 30 ], and more complex strategies (generally employing gravity-mediated settling) have recently been reported. Where efficiency has been reported, it has generally been low due to high cell loss during the process, which would nullify any potential benefit brought about by reaggregation [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…As has been alluded to throughout this review, the use of human insulin‐releasing cell lines could provide a potentially unlimited supply of beta‐cells for antidiabetic cell therapy. As evidenced by proof‐of‐principle studies using 1.1B4 and EndoC cells, generation of pseudoislets from suitable cell lines represents a promising approach, with the restoration of cell‐cell interactions likely to provide a physiological response more closely reminiscent of native islets . Furthermore, studies using animal cell lines indicate that pseudoislets exclusively comprised of beta‐cells show excellent functionality without connections to other islet cell types and that this can be enhanced substantially by transplantation to the rich in vivo mileau …”
Section: Islet Transplantation and New Therapeutic Approachesmentioning
confidence: 99%